Performance Based Seismic Retrofit Design of Brooklyn Basin Wharf - Sam Yao; Ali Naeem; Sara Barrett (Deep Foundations Institute, 2018)
Brooklyn Basin Project is a multi-billion-dollar development of the former Port of Oakland 9th Avenue Terminal located along the Oakland Estuary of California. A centerpiece of the development is the 10-acre shoreline park which will be built on a 1,200 ft long by 225 ft wide historic wharf. The wharf was built in the 1930’s on concrete and timber piles with a flat concrete slab. Prior to constructing the wharf, a rock dike was placed to protect the shoreline. The presence of the rock dike increased the hazards from lateral spreading of the underlying bay mud and non-ductile shear failure of piles driven through the dike. To open the park to the public, the wharf required a seismic retrofit in compliance with the California Building Code. The paper presents the results and conclusions of the following topics: • Structural condition assessment and repair strategies for the existing wharf deck, piles and jackets • Application of the California Building Code (CBC Ch31F) for the performance-based seismic evaluation of existing piers and wharves • Nonlinear pushover analysis of the wharf including the combination of inertial and kinematic effects • Impact of rock dike on lateral spreading and kinematic effects and the significance of existing piles in stabilizing the lateral spreading of the rock dike • Retrofit strategies for the wharf to meet the required seismic performance requirements per the California Building Code and reduce the demands on existing piles which were driven through the rock dike INTRODUCTION The 65-acre Brooklyn Basin Development project is located in Oakland, California. The project consists of 3,100 housing units, 200,000 sq. ft of retail and commercial space, along with various parks and public access improvements along the Oakland Estuary. A centerpiece of the development is the 10-acre Shoreline Park which will be built on a 1,200 ft long by 225 ft wide historic wharf. The wharf was built in the 1930’s on concrete and timber piles with a flat concrete slab. As shown in Figure 1, the wharf deck and piles support the 9th Avenue Terminal Building.